Papillary carcinoma of the thyroglossal duct cyst – Case report and literature review - Cardoso, Florinda (2019)
Papillary carcinoma of the thyroglossal canal is a malignant tumor that develops in the cyst of the thyroglossal canal. It is a rare entity, usually diagnosed in adulthood and is characterized by its benevolent behavior. We present this case by its rarity and presentation, and by the lack of consensus for definitive treatment.